10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Objectives Awareness of age-related change (AARC) reflects how individuals perceive age-related gains and losses, with positive perceptions consistently predicting better health and well-being. The Awareness of Age-Related Change theoretical framework has long highlighted physical and psychosocial health as distal antecedents of AARC, but their actual importance remains poorly understood. In this preregistered study, we empirically test this key model component. Methods We operationalize distal antecedents as 9-year trajectories in physical health (morbidity, grip strength, hearing, vision), cognitive functioning (recall, processing speed, working memory), and self-reported loneliness. We apply structural equation modeling to three-wave longitudinal data from the Berlin Aging Study II (N = 753, aged 61-81 at baseline, 49% female) and test if these trajectories predict late-life AARC. Results Older adults with better baseline recall and grip strength reported fewer AARC-losses, whereas those with higher baseline loneliness perceived more losses and fewer gains. Steeper declines in recall and stronger increases in morbidity were associated with heightened awareness of losses. Processing speed, working memory, hearing, and vision were not associated with AARC. Discussion Our results suggest several refinements of the Awareness of Age-Related Change framework: (a) within a given construct space (e.g., cognition), some dimensions (e.g., recall) are more strongly associated with perceiving age-related losses than others (e.g., processing speed), (b) long-term trajectories of recall memory and morbidity (rather than status alone) are particularly relevant for loss-focused awareness of aging, and (c) higher levels of loneliness are most consistently associated with awareness of age-related gains.